International capital markets : developments, prospects, and policy issues - Goldstein, Morris... et al. (IMF Washington, D.C.US, 1992)
Focuses on how to manage the restructuring of capital markets in an environment of wide-ranging liberalization, intense competition, and growing securitization - in a way that avoids a systematic crisis as well as moral hazard risks and budgetary costs associated with public sector support of weak financial institutions.